Association between plasma trimethylamine N-oxide level and atrial fibrillation - YANG Wentao, ZHAO Qing, LI Xiangdong, WANG Yutang, LIU Wei (Jichu yixue yu linchuang)
Objective To explore the relationship between plasma trimethylamine N-oxide(TMAO) level and atrial fibrillation(AF) by a clinical trial. Methods Totally 257 patients with AF were enrolled including 114 patients with paroxysmal AF and 143 with persistent AF. The control group had 122 non-AF patients; Plasma TMAO level, the demographic characteristics and clinical data of patients were collected. Regression analysis was performed to identify the association between TMAO and presence of AF. Results Plasma TMAO level of patients with AF was higher than that of patients without AF(3.9[2.4-5.9]vs. 2.4[1.6-3.7]μmol/L,P＜0.001);Even after adjust-ment of confounding factors including age, hypertension, diabetes, heart failure and body mass index; Plasma TMAO level was still related to presence of AF(OR:1.290,95% CI:1.151-1.445;P＜0.001).The plasma TMAO level of patients with persistent AF was higher than that of patients with paroxysmal AF(4.4[2.8-6.8]vs. 3.2[2.2-5.0]μmol/L,P＜0.01); Even after adjustment of confounding factors including age, hypertension, diabetes and heart failure and coronary heart disease; Plasma TMAO level was still related to persistent AF(OR:1.092,95% CI:1.009-1.182;P=0.029). Conclusions The level of plasma TMAO of patients with AF is higher than that of patients without AF. Elevated plasma TMAO level is related to an increased risk of AF. Elevated plasma TMAO level in patients with AF is related to an increased risk of persistent AF.